2009
DOI: 10.1590/s1415-47572009005000011
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the CCR5 gene coding region diversity in five South American populations reveals two new non-synonymous alleles in Amerindians and high CCR5*D32 frequency in Euro-Brazilians

Abstract: The CC chemokine receptor 5 (CCR5) molecule is an important co-receptor for HIV. The effect of the CCR5*D32 allele in susceptibility to HIV infection and AIDS disease is well known. Other alleles than CCR5*D32 have not been analysed before, neither in Amerindians nor in the majority of the populations all over the world. We investigated the distribution of the CCR5 coding region alleles in South Brazil and noticed a high CCR5*D32 frequency in the Euro-Brazilian population of the Paraná State (9.3%), which is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
9
1
Order By: Relevance
“…Remarkably, allele-D32 was more frequently found in individuals of European descent in southern Brazil. Boldt et al (2009) analyzed the distribution of this polymorphism in different ethnic groups residing in the State of Paraná in southern Brazil and found a frequency of 9.3% in a sample of 172 Euro-Brazilian individuals, which was significantly different from the population in this study (P < 0.05). Moreover, the frequency of this allele increased to 14.2% in a group of 53 Euro-Brazilian individuals whose ancestors were from or joined Mennonite settlements in southern Brazil (data not shown).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Remarkably, allele-D32 was more frequently found in individuals of European descent in southern Brazil. Boldt et al (2009) analyzed the distribution of this polymorphism in different ethnic groups residing in the State of Paraná in southern Brazil and found a frequency of 9.3% in a sample of 172 Euro-Brazilian individuals, which was significantly different from the population in this study (P < 0.05). Moreover, the frequency of this allele increased to 14.2% in a group of 53 Euro-Brazilian individuals whose ancestors were from or joined Mennonite settlements in southern Brazil (data not shown).…”
Section: Discussioncontrasting
confidence: 67%
“…The population of this state comprised 60% European, 21.5% African, and 18.5% indigenous peoples. The distribution of CCR5-D32 and CCR2-64I polymorphisms has been studied in different regions in Brazil (Acosta et al, 2003;De Pinho Lott Carvalhaes et al, 2004;Boldt et al, 2009); however, the frequencies of these polymorphisms in Piauí have not been reported. Therefore, in this study, we analyzed the prevalence of the CCR5-D32 and CCR2-V64I polymorphisms in a sample population in the State of Piauí and compared their frequencies to those observed in Brazil and other countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was absent among African and East Asian individuals (Table 3). Studies have shown that the percentages of L55Q polymorphism were found to be 7.8%, 3-4% and 2.7% among Tunisians, Caucasians and Euro-Brazilians, respectively (Table 3) (Boldt et al, 2009;Carrington et al, 1999;Jlizi et al, 2007). The group from Tunisia noticed high frequency of the L55Q variant among individuals of Berber origin (Jlizi et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…, 0.6% in Cepem, 0.7% in African-Brazilian populations from Pará (Carvalhaes et al , 2004), 0.9 and 1.0% in Bahia (Carvalho et al , 2004), 1.8% in Candelária and Bate-Estaca and 1.9% and 2.0% in African-Brazilian individuals in Rio de Janeiro (Chies and Hutz, 2003) and Paraná (Boldt et al , 2009), respectively. Among HIV + subjects, frequencies ranged from 2.1% in Rio de Janeiro (Teixeira et al , 2009) to 2.4% in Rio Grande do Sul (Vieira et al , 2011), 2.6% in a miscegenated population in Bahia (Grimaldi et al , 2002) and 3.8% in São Paulo (Rigato et al , 2008).…”
Section: Resultsmentioning
confidence: 99%